Changes in urinary titin N-terminal fragments as a biomarker of exercise-induced muscle damage in the repeated bout effect. Issue 6 (June 2020) - Yamaguchi, Shota; Suzuki, Katsuhiko; Kanda, Kazue; Inami, Takayuki; Okada, Junichi
Abstract: Objectives: Muscle damage symptoms induced by unaccustomed eccentric contraction exercise can be reduced by repeating the experience several times. This phenomenon is termed the repeated bout effect. Although traditional biochemical markers require invasive blood sampling, biochemical measurements have recently been developed that can be non-invasively performed using urinary titin N-terminal fragment (UTF). However, it is unclear whether UTF can reflect the repeated bout effect. Therefore, the aim of the present study was to clarify whether UTF decreased with the repeated bout effect. Design: This study compared changes in muscle damage markers between bouts of exercise performed for the first and second time. Methods: Eight young men performed 30 eccentric exercises of the elbow flexor on the first day of the first week (Bout 1). A second bout of eccentric exercises, same as the first, was performed 2 weeks later, (Bout 2). The dependent variables were muscle soreness (SOR), maximal voluntary isometric contraction (MVIC), range of motion (ROM), creatine kinase (CK), and UTF. All dependent variables were analyzed using two-way analysis of variance. Results: No significant difference was observed in workload or peak torque between the first and second exercise bouts. SOR as well as CK and UTF were significantly lower and ROM and MVIC were significantly higher in Bout 2 in comparison to Bout 1. Conclusions: These results suggest that UTF sensitively reflects the repeated bout effect and exercise-induced muscle damage can be non-invasively measured.